ABOUT THREE PROCESSES IN MATHEMATICS EDUCATION FOR SOLIDARITY ECONOMY ENTERPRISES - Renata Cristina Geromel Meneghetti; Geisa Zilli Shinkawa; Michelle Francisco de Azevedo; Ricardo Kucinskas (Editora da Universidade de Santa Cruz do Sul, 2013)
This paper focuses on Mathematics Education in the context of Solidarity Economy and aims to approach our performance, aiming to answer demands of Mathematics Education of the three Solidarity Economy Enterprises (SEE): a cooperative cleaning, of a women carpenter's group and a group manufacturing homemade soap. Based on the Ethnomathematics, a pedagogical intervention with these SEE was performed, in which we seek to work the Mathematics within the cultural context of these enterprises through problem situations related to their daily work. The research followed a qualitative research through action research. As a result we found that the approach applied has contributed to changes some attitudes, it was favorable to the learning of concepts and also the socioeconomic reintegration, in the direction of a posture more critical and emancipatory. The interventions were inserted in the Non Formal Education, and we point out that realize this type of education can indeed contribute to the ideals of Education in the Solidarity Economy as a way include those who have been socially excluded by formal education provided at school.